Postpartum Ovarian Function in Dairy Cattle - Mahaputra, Laba (1983)
To achieve the economic target of one calf a year, a cow must be pregnant by 85 days postpartum and is essential for maximum milk production. Resumption of ovarian activity and repro were investigated in ten normally calving cows from each of three breeds of cattle - Friesian, Jersey x LO and Friesian x Sahiwal. Visual observations, a teaser bull and tail painting wer detection. Rectal palpatian was conducted once weekly between 17 and 70 days postpartum and laparoscopic examination waw performed at least once during the experimental period to monitor ovarian changes. Samples of blood plasma were collected twice weekly during the same period from all cows and assayed for plasma progesterone using a radioimmunoassay. The non-detected aestrus, pregnancy and early embryonic mortality. A plasma progesterone concentration of 1 ng/ml or greater was used as the criterion for luteal activity. Intervals and standard deviations from parturition to first ovulation and first detected oestrus were 23 + 6.5 and 62 ± 25.9 days for Friesian, 29 + 9.9 and 33 ± 11.5 days for Jersey x LD and 48 + 29.1 and 59 ± 21.9 days for Friesian x Sahiwal cows. Interval from calving to the first postpartum ovulation and oestrus among three breeds were significantly different (p < 0.05). The interval from parturition to uterine involution for Friesian, Jersey x LD and Friesian x sahiwal were 35 ± 1.2, 33 ± 4.1 and 30 ± 2 days respectively (p> 0005). Only 52 percent of all cows were detected in oestrus at the commencement of the first aestrous cycle. The mean plasma progesterone concentration during detected oestrus was 0.23 ± 0.16 ng/ml and at 21 days for pregnant cows was 3.01 Z 0.89 ng/ml. Average plasma progesterone levels during oestrous cycle were highest in Friesian cows, moderate in Jersey x LD and lowest in Friesian x Sahiwal cows. Only one case of early embryonic death was recorded. Cystic ovaries were observed in 4 out of 10 Friesian cows. Sixty percent of Jersey x LD and 50 percent of Friesian x Sahiwal had conceived about day 85 postpartum. However, none of the Friesian cows had conceived by this time. The infertility in the Friesian cows were an oestrus, non-detected oestrus and repeat breeding which extended the calving interval beyond the optimum interval. The results confirm that Bos taurus x Bos indicus dairy breeds have a better reproductive performance than a Bos taurus breed in a tropical environment.